Analyzing sleep status in children with acute leukemia - Lu Xi; Guangsheng Wu; Xinke Du (BMC, 2023)
Abstract Background Quality sleep is essential for physical and mental health. We aimed to analyze sleep disorders in children with acute leukemia and explore associated factors. Methods General data and sleep disorders in children with acute leukemia during chemotherapy were collected by general questionnaires, Children's Sleep Disorders Scale and the Parenting Stress Index-short form. Results In total, 173 valid questionnaires were collected. The total Sleep Disorder Scale score > 39 is considered a sleep disorder, while sleep disorders accounted for 45.66% (79/173). In the cohort, 167 children had acute lymphoblastic leukemia, with 40.12% (67/167) having sleep disorders, while six children had acute non-lymphoblastic leukemia, with 50.00% (3/6) having sleep disorders. Single- and multi-factor regression analyses of age, gender, number of children in the family, and time spent using electronic devices showed that factors influencing sleep disorders in these children were mainly parental scolding and adenoid hypertrophy. Children with sleep disorders had more parental stress than those without sleep disorders (P < 0.05). Conclusions The high incidence of sleep disorders in children with acute leukemia is related to airway conditions and parental behaviors. Sleep disorders in children can increase parenting stress. Factors potentially affecting sleep quality should be addressed as early as possible, while parental education should be strengthened to better facilitate the physical and psychological recovery of their children.